Improved sperm cryosurvival in diluents containing amides versus glycerol in the Przewalski's horse (Equus ferus przewalskii) - Pukazhenthi, Budhan S.; Johnson, Aime; Guthrie, H. David; Songsasen, Nucharin; Padilla, Luis R.; Wolfe, Barbara A.; Coutinho da Silva, Marco; Alvarenga, Marco A. [UNESP]; Wildt, David E. (Elsevier, 2014)
Two studies were conducted to understand sperm cryosensitivity in an endangered equid, the Przewalski's horse (Equus ferus przewalski), while testing the cryoprotectant ability of formamides. The first assessed the toxicity of permeating cryoprotectants (glycerol, methylformamide [MF] and dimethylformamide [DMF]) to Przewalski's horse spermatozoa during liquid storage at 4. °C. The second examined the comparative influence of three diluents (with or without formamides) on cryosurvival of sperm from the Przewalski's versus domestic horse. When Przewalski's horse spermatozoa were incubated at 4. °C in INRA 96 with differing concentrations of glycerol, MF or DMF or a combination of these amides, cells tolerated all but the highest concentration (10% v/v) of MF alone or in combination with DMF, both of which decreased (P<. 0.05) motility traits. There was no effect of cryoprotectants on sperm acrosomal integrity. In the cryosurvival study, average sperm motility and proportion of cells with intact acrosomes in fresh ejaculates were similar (P>. 0.05) between the Przewalski's (67%, 84%, respectively) and domestic (66%, 76%) horse donors. Sperm from both species were diluted in lactose-EDTA-glycerol (EQ), Botu-Crio (BOTU; a proprietary product containing glycerol and MF) or SM (INRA 96 plus 2% [v/v] egg yolk and 2.5% [v/v] MF and DMF) and then frozen over liquid nitrogen vapor. After thawing, the highest values recovered for total and progressive sperm motility, acrosomal integrity and mitochondrial membrane potential were 42.4%, 21.8%, 88.7% and 25.4. CN (CN. = mean JC-1 fluorescence intensity/cell on a channel number scale), respectively, in the Przewalski's and 49.3%, 24.6%, 88.9% and 25.8. CN, respectively, in the domestic horse. Although sperm progressive motility and acrosome integrity did not differ (P>. 0.05) among treatments across species, mitochondrial membrane potential was higher (P<. 0.05) in both species using EQ compared to BOTU or SM media. Additionally, Przewalski's stallion sperm expressed higher (P<. 0.05) post-thaw total motility in BOTU and SM compared to EQ, whereas there were no differences among freezing diluents in the domestic horse. In summary, Przewalski's stallion sperm benefit from exposure to either MF or DMF as an alternative cryoprotectant to glycerol. Overt sperm quality appears similar between the Przewalski's and domestic horse, although the total motility of cells from the former appears more sensitive to certain freezing diluents. Nonetheless, post-thaw motility and acrosomal integrity values for Przewalski's horse spermatozoa mimic findings in the domestic horse in the presence of INRA 96 supplemented with 2% (v/v) egg yolk and a combined 2.5% concentration of MF and DMF. © 2014.
Keywords: Cryoprotectant; Equid; Freezing; Mitochondria; Semen; Spermatozoa